POTENCY OF RAMIN (Gonystylus bancanus Kurtz.) AND OTHER COMMERCIAL SPECIES IN PEAT SWAMP FOREST MANAGED WITH TPTI SILVICULTURAL SYSTEM IN BAGAN, RIAU - Hendromono Hendromono (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2005)
Ramin (Gonystylus bancanus Kurtz.) is one of the tree species in peat-swamp forest that is endangered due to excessive exploitation. The objective of this research was to assess the potency of rarnin and other commercial tree species in primary and logged over peat-swamp forests at Bagan, Riau. The tree stands were inventoried in primary forest of the 2004 and 2006 Annual Work Plan (RKTs) and in the 1997 and 2001 RKTs managed with Indonesian Selective Cutting and Planting (TPTI) silvicultural system. The result showed that rarnin in Bagan peat-swamp forest was not evenly distributed. The total number of ramin in tree stage in primary forests was fewer than that in logged over forests. The total number of ramin species at tree stage in primary forest was between 4.5 and 5 trees ha·' with the important value index (IVI) of 10.3 to 12.0%, whereas the one at logged over forest were between 2.5 and 15 trees ha·' with theM indices of 7.9 to 20.4%. Commercial species of swamp meranti (Shorea uliginosaand S. teysmaniana) and balam/ suntai or (Palaqqiumspp.) were dominant at tree stage both in the primary and the logged over forests. Enrichment in logged over forests is not needed since the total number of seedlings and saplings is enough. The total number of potential core trees in logged over forests was enough for the next cutting cycle. The effort that must be done in logged over forests is to protect them from illegal logging.